Id-1 expression in colorectal adenocarcinoma tissues and its clinical significance - Wu,Xue-Liang (2019)
SUMMARY BACKGROUND: This study aims to investigate the expression of Id-1 in human colorectal adenocarcinoma tissues and explore its correlation with the clinical pathological parameters of colorectal cancer. METHODS: The Id-1 mRNA and protein expression levels of 50 specimens of normal colorectal tissues and 50 specimens of colorectal adenocarcinoma tissues were detected using reverse-transcription polymerase chain reaction and western blot. Furthermore, Id-1 protein was detected using immunohistochemistry. The correlation between the expression of Id-1 and clinicopathologic features was analyzed. RESULTS: The mRNA expression level of Id-1 in colorectal adenocarcinoma tissues and normal colorectal tissues was 0.96 ± 0.03 vs. 0.20 ± 0.04, respectively; and the difference was statistically significant (P=0.011). Furthermore, Id-1 protein expression was higher in colorectal adenocarcinoma tissues than in normal colorectal tissues (0.82 ± 0.04 vs. 0.31 ± 0.02, P=0.020). In addition, the positive protein expression rate of Id-1 was higher in colorectal adenocarcinoma tissues than in normal colorectal tissues (72.00% vs. 24.00%, X2=23.431, P=0.000). The expression of Id-1 was correlated with the depth of tumor invasion, TNM stage, lymph node metastasis, vessel invasion, and liver metastasis (P<0.01). However, this expression was not correlated with tumor size and differentiation degrees (P>0.05). CONCLUSIONS: The high Id-1 expression in colorectal adenocarcinoma tissues play an important role in the process of cancer, and is expected to become a new tumor monitoring indicator for clinical diagnosis, treatment, and prognosis judgment.